Web-Based Guided Self-Help Acceptance and Commitment Therapy (ACT) to Increase Self-Compassion and Psychological Flexibility in Psychology Undergraduates Suffering Emotional Distress: A Feasibility Study: [Guided Self-Help Acceptance and Commitment Therapy (ACT) Berbasis-Web untuk Meningkatkan Self-Compassion dan Fleksibilitas Psikologis pada Mahasiswa Sarjana Psikologi dengan Distress Emotional: Studi Fisibilitas] - Gunawan, Felicia Yosiana; Oriza, Imelda Ika Dian (ANIMA Indonesian Psychological Journal, 2022)
Emotional distress amongst university students is an issue which has emerged as the result of various factors, such as the transition from adolescence to young adulthood, an increase in demands made, and changes in the situation and the system of learning. The phenomenon of distress may be seen from the number of undergraduate students seeking psychological help in university clinics. The queues of undergraduates always exceed the capacity for the provision of services, so that undergraduates are forced to wait for between one and three months. One of the ways to overcome this phenomenon is by conducting web-based psychological intervention. Internet connection may increase accessibility and facilitation of web-based psychological intervention. This study examined the feasibility of eight sessions of web-based guided self-help Acceptance and Commitment Therapy (ACT) organized to reduce the levels of emotional distress and to increase the psychological flexibility and self-compassion of undergraduate students of the Faculty of Psychology of a university in Indonesia. This study was quasi-experimental, with a one group pretest-posttest design involving 38 participants. After the interventions, there was a significant reduction in symptoms of distress detected, as well as an increase in the levels of psychological flexibility and self-compassion of the participants. Feasibility assessment results showed that with the supportive resources of the people conducting the trial, Internet connections, and independence on the part of the participants, the conducting of a web-based program of Acceptance and Commitment Therapy (ACT) is feasible. More in-depth research on a wider scale is required to reach a closer to adequate conclusion regarding the effectiveness of such a program, however, the feasibility of the web-based Acceptance and Commitment Therapy (ACT) intervention, as proven in this study, indicated that the features of online psychological intervention offer an efficient option for the providers of mental health services. Distress emosional pada mahasiswa adalah isu yang muncul akibat berbagai faktor, seperti transisi dari usia remaja ke dewasa muda, bertambahnya tuntutan, dan perubahan situasi serta sistem belajar. Fenomena distress terlihat dari banyaknya mahasiswa sarjana yang mencari bantuan psikologis di klinik universitas. Antrean mahasiswa selalu melebihi kapasitas pemberi layanan sehingga mahasiswa perlu mengantre selama satu hingga tiga bulan. Salah satu cara untuk mengatasi fenomena ini adalah dengan menjalankan intervensi psikologis berbasis-web. Koneksi Internet dapat meningkatkan keterjangkauan dan kemudahan partisipan mengakses layanan psikologis. Studi ini meneliti fisibilitas delapan sesi guided self-help Acceptance and Commitment Therapy (ACT) berbasis-web yang disusun untuk menurunkan tingkat distress emosional serta meningkatkan fleksibilitas psikologis dan self-compassion mahasiswa sarjana Fakultas Psikologi dari sebuah universitas di Indonesia. Studi ini merupakan quasi-experimental dengan desain one-group pretest-posttest sebanyak 38 partisipan. Setelah intervensi, ditemukan penurunan gejala distress yang signifikan, disertai dengan naiknya fleksibilitas psikologis dan self-compassion partisipan. Hasil asesmen fisibilitas menunjukkan bahwa dengan sumber daya yang menunjang dari pihak pelaksana, koneksi Internet, dan kemandirian dari pihak partisipan, program Acceptance and Commitment Therapy (ACT) berbasis-web fisibel untuk dilakukan. Riset lebih dalam dengan skala lebih luas dibutuhkan untuk mencapai konklusi yang lebih adekuat mengenai efektivitas program, namun fisibilitas intervensi Acceptance and Commitment Therapy (ACT) berbasis-web yang terbukti pada studi ini menunjukkan bahwa intervensi psikologis fitur daring merupakan opsi efisien bagi penyedia layanan kesehatan mental.